Letter (copy) : Food for Spain - Tewson, Vincent
030-0216-001 HVT/FC/EK/503. Secretary's. 1st February, 1938. Mr. W. Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Schevenels, FOOD FOR SPAIN. Many thanks for your letter of yesterday in regard to the above subject. The particulars you send are very useful. I note that you state that all the goods distributed are labelled as coming from the International Solidarity Fund. In actual practice, however, the people who see the labels may not know anything at all about those who are responsible for the fund. Do you think it would be possible to include on the labels some explanation that the fund represents contributions from workers in countries affiliated to the International Federation of Trade Unions and the Labour and Socialist International? I know we do not want a label in the form of a propaganda poster, but probably if there were some wording in small type it would be helpful. Perhaps this wording is already on the label in which case it is difficult to see how we could do more without being guilty of the blatant advertising which has been the subject of comment in the case of some other organisations. Yours sincerely, Assistant Secretary. 292/946/30/216